From Lab to Field: Role of Humic Substances Under Open-Field and Greenhouse Conditions as Biostimulant and Biocontrol Agent - Jindo, Keiji; Olivares, Fábio Lopes; Malcher, Deyse Jacqueline da Paixão; Sánchez-Monedero, Miguel Angel; Kempenaar, Corné; Canellas, Luciano Pasqualoto (Frontiers in Plant Science, 2020)
The demand for biostimulants has been growing at an annual rate of 10% and 12.4% in Europe and Northern America, respectively. The beneficial effects of humic substances (HS) as biostimulants of plant growth have been well-known since the 1980s, and they can be supportive to a circular economy if they are extracted from different renewable resources of organic matter including harvest residues, wastewater, sewage sludge and manure. This paper presents an overview of the scientific outputs on application methods of HS in different conditions. Firstly, the functionality of HS in the primary and secondary metabolism under stressed and not-stressed cropping conditions are discussed along with crop protection against pathogens. Secondly, the advantages and limitations of five different types of HS application under open-fields and greenhouse conditions are described. Key factors such as the chemical structure of HS, application method, optimal rate and field circumstances, play a crucial role in enhancing plant growth by HS treatment as a biostimulant. If we can get a better grip on these factors, HS has the potential to become a part of circular agriculture.